1999
DOI: 10.1016/s0140-6736(98)11392-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of psychological response on survival in breast cancer: a population-based cohort study

Abstract: S u m m a r y B a c k g r o u n d The psychological response to breast cancer, such as a fighting spirit or an attitude of helplessness and hopelessness toward the disease, has been suggested as a prognostic factor with an influence on survival. We have investigated the effect of psychological response on disease outcome in a large cohort of women with early-stage breast c a n c e r . M e t h o d s 578 women with early-stage breast cancer were enrolled in a prospective survival study. Psychological response wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
337
6
28

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 631 publications
(387 citation statements)
references
References 18 publications
16
337
6
28
Order By: Relevance
“…As in previous research, we identified only one protective psychological factor, a coping pattern Distancing, which is close to minimising (see footnote c). Denying or minimising the fact of having the cancer has long been suggested to be a predictor of a favourable cancer prognosis (Greer et al, 1979(Greer et al, , 1990Butow et al, 1999;Watson et al, 1999;Butow et al, 2000;Petticrew et al, 2002;Garssen, 2004;Lehto et al, 2006). Minimising the impact of the diagnosis is milder and nowadays a more realistic form of denial (Garssen, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As in previous research, we identified only one protective psychological factor, a coping pattern Distancing, which is close to minimising (see footnote c). Denying or minimising the fact of having the cancer has long been suggested to be a predictor of a favourable cancer prognosis (Greer et al, 1979(Greer et al, , 1990Butow et al, 1999;Watson et al, 1999;Butow et al, 2000;Petticrew et al, 2002;Garssen, 2004;Lehto et al, 2006). Minimising the impact of the diagnosis is milder and nowadays a more realistic form of denial (Garssen, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of psychosocial factors on cancer progression has been investigated in a number of studies (Greer et al, 1979(Greer et al, , 1990Pettingale et al, 1985;Gross, 1989;Spiegel et al, 1989;Forsen, 1991;Barraclough et al, 1992;Blanchard et al, 1995;Maunsell et al, 1995;Dolbeaut et al, 1999;Watson et al, 1999;Butow et al, 2000;Reynolds et al, 2000;Spiegel, 2001;Petticrew et al, 2002;Garssen, 2004) and many of these have dealt with breast cancer (Greer et al, 1979(Greer et al, , 1990Pettingale et al, 1985;Spiegel et al, 1989;Forsen, 1991;Barraclough et al, 1992;Maunsell et al, 1995;Watson et al, 1999;Butow et al, 2000;Reynolds et al, 2000;Garssen, 2004). However, the contributing factors are uncertain, and there is also a lack of understanding of the psychological processes and the psychobiological mechanisms involved (Garssen and Goodkin, 1999).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 In response, various supportive psychosocial intervention strategies have been designed, tailored to the problems that cancer patients face during the course of their disease. [3][4][5][6] The extent to which cancer affects not only patients but also their closest relatives was first addressed in a seminal article published more than 20 years ago, in which House et al illustrated how several diseases can influence people close to the patient. 7 The mechanism of this effect may involve several interacting pathways: the event may cause stress in the partner; it might deprive the partner of emotional, social, and economic support; and it can influence the daily life and behavior of the partner.…”
mentioning
confidence: 99%